Meandering-trapezoidal shaped MEMS structure for low frequency vibration based energy harvesting applications. (December 2020) - Debnath, Bapi; Kumar, R.; Mohamed Shakeel, P.
Abstract: In this study, we explore the design of new two highly symmetric springs of Meandering-Trapezoidal shaped microelectromechanical system (MEMS) structure based biosensor application with a single proof mass for low frequency vibration based energy harvesting applications. The related harvester design and output were obtained and validated by means of finite elements analysis (FEA) and finite element method (FEM) simulations. We use four different kind of piezoelectric material such as PZT-5A, ZnO, AlN, PVDF on the same dimension of Meandering-Trapezoidal shaped springs and analyze the FEA and FEM output. The maximum output power using PZT-5A, ZnO, AlN, PVDF piezoelectric materials are 117.55 nW, 44.37 nW, 10.58 nW, 0.55 nW over 35.9 Hz, 40.7 Hz, 49.7 Hz, 29.7 Hz resonant frequency, respectively at input acceleration of 0.1 g. From the comparative study, we obtain that piezoelectric material PZT-5A on Meandering-Trapezoidal spring design imply better potential generation.